Penerapan Model Make a Match Berbasis Saintifik Untuk Meningkatkan Hasil Belajar Tematik Siswa - Shafira Dwintha Aulia; Wahyudi Wahyudi; Indri Purwanti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2018)
This research aims to improve the thematic learning outcomes of grade 1 students of SDN Salatiga 05 by implementing the Make a Match model based on scientific. Type of this research is class action research with Stringer model includes look, think and act. Data collection instruments used formative tests, observation, and field notes. Analysis techniques using comparative descriptive. The subjects of research were students of grade 1 SDN Salatiga 05. The results of the study found an increase in the percentage of the students learning activities in the first cycle of 79,35% and the second cycle increased to 84,71%. Students activities increased have an impact on thematic learning outcomes completeness shown in the first cycle of 71%, and increased to 86% in the second cycle. Based on these results, the Make a Match model based on scientific can improve students thematic learning outcomes.